Departing from deviance : a history of homosexual rights and emancipatory science in America - Minton, Henry L. (University of Chicago Press, 2002)
The struggle to remove the stigma of sickness surrounding same-sex love has a long history. In 1973, the American Psychiatric Association removed homosexuality from its diagnostic classification of mental illness, but the groundwork for this pivotal decision was laid decades earlier. In this new study, Henry L. Minton looks back at the struggle of the American gay and lesbian activists who chose scientific research as a path for advancing homosexual rights. He traces the history of gay and lesbian emancipatory research from its early beginnings in the late nineteenth century to its role in cha.